Young and/but successful: business graduates performing themselves as valuable labouring subjects - Korhonen Maija; Siivonen Päivi; Isopahkala-Bouret Ulpukka; Mutanen Heli; Komulainen Katri (Routledge, Taylor & Francis Group, 2025)
This article advances critical theoretical and methodological approaches to employability. From the perspectives of neoliberal governmentality and positioning analysis, we investigate graduate employability as a process of creating value for the self in the labour markets. The study analyses how young Finnish business graduates (n = 19) who work in business organisations perform themselves as valuable labouring subjects in their interviews. Based on our analysis, we develop an argument that being a young business professional is simultaneously presented as a problem and a virtue in terms of a valuable labouring subject. The analysis shows that graduates cultivate themselves as easily employable, mature job seekers and successful young employees equipped with personal social skills, enthusiasm and youthful energy and drive. They draw on the neoliberal discourse of employability to negotiate issues identified as problematic – their young age and lack of work experience – in terms of their value. Their performances of the self are thus purposeful responses to the contextual expectations and pressures they encounter while competing for jobs and striving to gain recognition as novice professionals in organisations. The study reveals that graduates’ whole subjectivity is at the core of the process of value creation in contemporary labour markets.